IMPLEMENTASI METODE PEMBIASAAN STRATA BAHASA JAWA SEBAGAI SARANA MELESTARIKAN NILAI-NILAI BUDAYA JAWA - Fitrianingsih, Ely; Nasokha, Nasokha; Hidayat, Muhtar Sofwan (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2020)
The purpose of this research are to 1) find the implementation of the Javanese language strata at MI Ma'arif Kliwonan, 2) find what are the supporting and inhibiting factors in the implementation of the language strata habituation method and how to solve, and 3) find the implementation of the language strata habituation method can be said as a means of preserving Javanese cultural values. The type of research used is descriptive qualitative research. Data collection used participant observation and in-depth interviews. The result study showed method of habituation to the Javanese language strata which is carried out routinely and programmed, students are able to inherit Javanese cultural values ​​which have recently almost faded. so that the younger generation no longer feels ashamed to use the richness of culture to communicate using the good and correct Javanese language. The method of habituation of Javanese language strata is used as a means of preserving Javanese cultural values ​​in general, namely as a liaison for the destruction of Javanese culture in the era of globalization.